2017
DOI: 10.1039/c6cc08381a
|View full text |Cite
|
Sign up to set email alerts
|

Human carnitine biosynthesis proceeds via (2S,3S)-3-hydroxy-Nε-trimethyllysine

Abstract: The stereochemistry of human trimethyllysine hydroxylase was determined to be (2S,3S)-3-hydroxy-N ε-trimethyllysine by comparison to asymmetrically synthesised (2S,3R)-3-hydroxy-N ε-trimethyllysine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…20). Comparison with a diastereomeric mixture of C3 hydroxylysine isomers and synthetic (2 S ,3 R )/(2 R ,3 S )-hydroxylysine standard27 identified (2 S , 3S )-hydroxylysine as the JMJD7-catalyzed product (Fig. 4b and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…20). Comparison with a diastereomeric mixture of C3 hydroxylysine isomers and synthetic (2 S ,3 R )/(2 R ,3 S )-hydroxylysine standard27 identified (2 S , 3S )-hydroxylysine as the JMJD7-catalyzed product (Fig. 4b and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
“…C3, C4, and C5 hydroxylysine standards were synthesized or commercially obtained as described14. The synthesis of the (2 S ,3 R )/(2 R ,2 S )-3-hydroxylysine standard has been reported elsewhere27.…”
Section: Methodsmentioning
confidence: 99%
“…The (2S,3S) stereochemistry of the TMLH-catalyzed product was established through both synthetic and NMR-based investigations ( Figure 2 ) [ 32 , 43 ]. The synthetic (2S,3S)-3-hydroxylysine and (2S,3R)-3-hydroxylysine were used as standards for comparison to the product formed in the presence of the recombinant TMLH.…”
Section: Carnitine Biosynthesismentioning
confidence: 99%
“…As an aside it is notable that the role of TML in the carnitine biosynthesis pathway provides a potentially direct link between histone modification status (and, hence, epigenetics) and fatty acid metabolism. The stereochemistry of the BBOX and TMLH catalysed reactions are conserved with respect to the N ϵ ‐trimethyl‐ and carboxylate groups in their substrates, consistent with a common evolutionary origin. This proposal is supported by sequence analyses based on crystallographic studies on BBOX, which revealed a dimeric structure, and contrasts with the monomeric nature of IPNS/DAOCS subfamily oxygenases.…”
Section: Functional Assignment Of 2og Oxygenases In Metabolismmentioning
confidence: 62%
“…The small molecule starting point for carnitine biosynthesis is N ϵ ‐trimethyl lysine (TML) which is produced via protein degradation, likely substantially from N ‐methylated histones. Trimethyllysine hydroxylase (TMLH) catalyses ( 3S )‐hydroxylation of TML to give (2 S ,3 S )‐3‐hydroxy‐ N ϵ ‐trimethyllysine, which undergoes transformation to γ‐butyrobetaine, which further undergoes (3 R )‐hydroxylation as catalysed by γ‐butyrobetaine hydroxylase (BBOX) to give carnitine (Figure A). As an aside it is notable that the role of TML in the carnitine biosynthesis pathway provides a potentially direct link between histone modification status (and, hence, epigenetics) and fatty acid metabolism.…”
Section: Functional Assignment Of 2og Oxygenases In Metabolismmentioning
confidence: 99%